Core-shell type catalyst carrier as well as preparation method and application thereof
By combining the support material of the support with a specific roughness and the active component supported layer material with particle size distribution on the catalyst support, the spherical catalyst support is solved, and the problems of peeling and wear of the existing catalyst surface coating are reduced, and the platinum-based metals are reduced. Loss has improved the catalyst usage effect and resource utilization rate.
Patent Information
- Application Number
- CN202310785429.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The existing coating-type catalysts are prone to peeling and wear on the surface coating during transportation, filling and use, resulting in the loss of precious platinum-based metal active components, affecting the catalyst effect and economic loss of resources.
Using a core-shell catalyst support, a spherical catalyst support with a surface roughness of 900nm-1900nm is formed by combining a support with a specific roughness and a supporting layer material with a specific particle size distribution, thereby reducing the peeling and wear of the active components. .
It effectively reduces the loss of platinum-based metal active components, improves the use effect of catalysts and resource utilization.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a core-shell catalyst carrier and a preparation method and application thereof. Background Art
[0002] The catalytically active components of existing coated carrier catalysts are distributed on the surface of the catalyst and are exposed. During the transportation, filling and use of the catalyst, the friction between the catalyst particles, the collision and friction between the catalyst and the equipment, and the long-term erosion of the catalyst by the reaction gas will inevitably cause the coating on the catalyst surface to peel off and wear. The peeling and wear of the catalyst surface coating will cause the loss of active components, especially the loss of expensive platinum metals such as platinum, which not only affects the use effect of the catalyst, but also causes resource and economic losses. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a core-shell catalyst carrier with a certain surface roughness, which is composed of a support body with a specific roughness and an active component support layer material with a specific particle size distribution, and the active component support layer on the outer surface is not easy to peel off from the support body. The catalyst prepared using the carrier has a support layer containing platinum metals that is not easy to wear and peel off, thereby reducing the loss of platinum metal active components.
[0004] In the first aspect, the present invention provides a core-shell catalyst carrier, comprising a spherical support body and an active component loading layer wrapped around the outer surface of the spherical support body, wherein the surface roughness Ra value of the catalyst carrier is 900nm-1900nm, and / or the surface roughness Rz value of the catalyst carrier is 5000nm-10000nm.
[0005] In some embodiments, the surface roughness Ra value of the catalyst carrier is 900nm, 1100nm, 1300nm, 1500nm, 1700nm, 1900nm or any value therebetween. In some preferred embodiments, the surface roughness Ra value of the catalyst carrier is 1400nm-1800nm.
[0006] In some embodiments, the surface roughness Rz value of the catalyst carrier is 5000nm, 6000nm, 7000nm, 8000nm, 9000nm, 10000nm or any value therebetween. In some preferred embodiments, the surface roughness Rz value of the catalyst carrier is 7000nm-9000nm.
[0007] In some embodiments, the diameter of the catalyst carrier is 1-10 mm, for example, 2 mm, 4 mm, 6 mm, 8 mm, 10 mm or any value therebetween. In some preferred embodiments, the diameter of the catalyst carrier is 2 mm-5 mm.
[0008] In some embodiments, the spherical support is selected from at least one of α-alumina, silicon carbide, spinel, mullite, or cordierite.
[0009] In some embodiments, the active component supporting layer is selected from at least one of γ-alumina, δ-alumina, θ-alumina or molecular sieves. In some embodiments, the active component supporting layer is γ-alumina.
[0010] In some embodiments, the weight ratio of the spherical support to the active component loading layer is (2-15):1, for example, 3:1, 5:1, 7:1, 9:1, 11:1, 13:1, 15:1 or any value therebetween. In some preferred embodiments, the weight ratio of the spherical support to the active component loading layer is (3-9):1, in weight percentage.
[0011] In a second aspect, the present invention provides a method for preparing a core-shell catalyst carrier, comprising the following steps:
[0012] (a) preparing a spherical support, wherein the surface roughness Ra value of the spherical support is between 1900nm and 2900nm, and the Rz value is between 10000nm and 20000nm;
[0013] (b) Wrapping the active component loading layer material onto the surface of the spherical support.
[0014] In some embodiments, in step (a), the preparation of the spherical support comprises: preparing powder of the support material into spherical particles, and then calcining the spherical particles.
[0015] In some embodiments, the calcination temperature is 800°C-1400°C, for example, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or any value therebetween. In some preferred embodiments, the calcination temperature is 950°C-1300°C.
[0016] In some embodiments, the calcination time is 2h-24h, for example, 2h, 5h, 8h, 10h, 12h, 15h, 18h, 20h, 24h or any value therebetween. In some preferred embodiments, the calcination time is 4h-12h.
[0017] In some embodiments, the particle size of the support material is less than 100 mesh, preferably 300 mesh to 400 mesh.
[0018] In some embodiments, the surface roughness Ra value of the spherical support is 1900nm, 2100nm, 2300nm, 2500nm, 2700nm, 2900nm or any value therebetween. In some embodiments, the surface roughness Ra value of the spherical support is 2100nm-2500nm.
[0019] In some embodiments, the surface roughness Rz value of the spherical support is 10000nm, 12000nm, 14000nm, 14500nm, 16000nm, 18000nm, 20000nm or any value therebetween. In some preferred embodiments, the surface roughness Rz of the spherical support is 11000nm-16500nm.
[0020] In some embodiments, in step (b), the encapsulation is achieved by dip-coating or spray-coating the spherical support with a solution containing active component loading layer materials.
[0021] In some embodiments, the solution containing the active component supporting layer material is obtained by wet ball milling.
[0022] In some embodiments, in the active component loading layer material, particles with a diameter less than 2 μm account for less than 10%, particles with a diameter of 2-15 μm account for 75%-90%, and particles with a diameter greater than 15 μm account for 5%-20%.
[0023] In a third aspect, the present invention provides a spherical catalyst, comprising the catalyst carrier described in the first aspect or the catalyst carrier obtained by the preparation method described in the second aspect, and a platinum group metal supported on the catalyst carrier.
[0024] In some embodiments, the platinum group metal is selected from one or more of ruthenium, rhodium, osmium, platinum and palladium, preferably platinum.
[0025] In some embodiments, the weight of the platinum group metal is 0.01%-5.0% of the weight of the spherical catalyst, for example, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or any value therebetween. In some preferred embodiments, the weight of the platinum group metal is 0.05%-1.0% of the weight of the spherical catalyst.
[0026] In a fourth aspect, the present invention provides a method for preparing a spherical catalyst, comprising impregnating the catalyst carrier described in the first aspect or the catalyst carrier obtained by the preparation method described in the second aspect in an aqueous solution containing a platinum group metal element compound, followed by drying and calcining.
[0027] In some embodiments, the drying temperature is 60°C-200°C, for example, 60°C, 100°C, 140°C, 180°C, 200°C or any value therebetween.
[0028] In some embodiments, the drying time is 2-24 h, for example, 2 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 24 h or any value therebetween.
[0029] In some embodiments, the calcination temperature is 400°C-800°C, for example, 400°C, 500°C, 600°C, 700°C, 800°C or any value therebetween.
[0030] In some embodiments, the calcination time is 2-12 h, for example, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h or any value therebetween.
[0031] In a fifth aspect, the present invention provides a method for producing unsaturated hydrocarbons by dehydrogenating saturated hydrocarbons, comprising subjecting hydrogen produced by dehydrogenating saturated hydrocarbons to a selective oxidation reaction in the presence of the catalyst described in the third aspect or the catalyst obtained by the preparation method of the fourth aspect.
[0032] In some embodiments, the selective oxidation reaction conditions include a reaction temperature of 520-650°C, a reaction pressure of 20-200 KPa, and a liquid reaction space velocity of 0.1-10 h -1 .
[0033] The core-shell catalyst carrier of the present invention is formed by combining a support body with a specific roughness and an active component support layer material with a specific particle size distribution, and the active component support layer on the outer surface is not easy to peel off from the support body. The catalyst prepared by using the carrier has a support layer containing platinum metals that is not easy to wear and peel off, thereby reducing the loss of platinum metal active components. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0035] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0036] The present invention will be described in detail below through examples.
[0037] In the method of the present invention, the surface roughness Ra and Rz are tested by Mitutoyo surface roughness tester SJ-411, and the test conditions are as follows: test speed: 0.5 mm / s; recovery speed: 2.0 mm / s; probe 12AAC731. The evaluation conditions are as follows: standard: ISO1997; curve type: R; filter: GAUSS; Λc: 0.25 mm; Λs: 2.5 μm; profile compensation: circle. Among them, Ra represents the arithmetic mean of the absolute value of the profile deviation within the sampling length L, and Rz represents the sum of the average value of the 5 largest profile peak heights and the average value of the 5 largest profile valley depths within the sampling length.
[0038] In the method of the present invention, the particle size distribution is tested by Malvern MasterSizer 2000, and water is used as a dispersant to perform a wet test.
[0039] The reagents used in the following examples are commercially available and of analytical grade.
[0040] Example 1
[0041] 1 kg of 300-mesh cordierite powder was extruded to form spherical particles with a diameter of 3 mm. After drying, the spherical particles were calcined at 1300°C for 8 hours and cooled to obtain a spherical support. The surface roughness of the spherical support was tested with a surface roughness tester, and the Ra was 2400 nm and the Rz was 13670 nm.
[0042] Take 20g of γ-alumina, add water and wet ball mill to obtain a γ-alumina suspension aqueous solution. The particle size distribution of γ-alumina in the suspension is measured to be 4.1% of particles less than 2μm, 88.5% of particles with a particle size of 2-15μm, and 7.4% of particles with a particle size greater than 15μm. Take 80g of the above spherical support, spray the γ-alumina suspension aqueous solution onto the spherical support by atomization coating, and obtain a spherical catalyst carrier a1 with a shell structure after drying and calcining. The surface roughness of the carrier a1 is measured, Ra is 1447nm, and Rz is 7949nm.
[0043] Dissolve chloroplatinic acid in water to prepare a solution with a platinum content of 25.0 mg / mL. Immerse 10 g of a spherical catalyst carrier a with a shell structure in a chloroplatinic acid solution of equal volume to the carrier, then dry at 120°C for 4 hours, and calcine at 600°C for 6 hours to obtain a spherical catalyst A1 with a shell structure and a platinum content of 0.20% by mass.
[0044] The attrition rate of the spherical catalyst A1 with a shell structure was measured according to the method of standard HG / T 2976-1999, and was 0.18%. The powder ground during the attrition rate test was collected and the mass fraction of platinum in the powder was measured by elemental analysis, and was 0.97%. The loss rate of the active component platinum was 0.87%.
[0045] Example 2
[0046] 1 kg of 300-mesh cordierite powder was extruded to form spherical particles with a diameter of 3 mm. After drying, the spherical particles were calcined at 1100°C for 8 hours and cooled to obtain a spherical support. The surface roughness of the spherical support was tested with a surface roughness tester, and the Ra was 2483 nm and the Rz was 14473 nm.
[0047] The carrier a2 was prepared in the same manner as in Example 1. The surface roughness of the carrier a2 was measured, and Ra was 1762 nm and Rz was 8762 nm. The corresponding catalyst was prepared in the same manner as in Example 1 to obtain catalyst A2.
[0048] The attrition rate of catalyst A2 was measured according to the method of standard HG / T 2976-1999, and the attrition rate was 0.14%. The powder ground off during the attrition rate test was collected and the mass fraction of platinum in the powder was measured by elemental analysis, and the mass fraction was 0.98%. The loss rate of active component platinum was 0.69%.
[0049] Example 3
[0050] 1 kg of 300-mesh cordierite powder was extruded to form spherical particles with a diameter of 3 mm. After drying, the spherical particles were calcined at 950°C for 8 hours and cooled to obtain a spherical support. The surface roughness of the spherical support was tested with a surface roughness tester, and the Ra was 2461 nm and the Rz was 13763 nm.
[0051] The carrier a3 was prepared in the same manner as in Example 1. The surface roughness of the carrier a3 was measured, and Ra was 1512 nm and Rz was 8312 nm. The corresponding catalyst was prepared in the same manner as in Example 1 to obtain catalyst A3.
[0052] The attrition rate of catalyst A3 was measured according to the method of standard HG / T 2976-1999, and it was 0.17%. The powder ground off during the attrition rate test was collected, and the mass fraction of platinum in the powder was measured by elemental analysis, and it was 0.96%. The loss rate of active component platinum was 0.82%.
[0053] Example 4
[0054] 1 kg of 300-mesh cordierite powder was extruded to form spherical particles with a diameter of 3 mm. After drying, the spherical particles were calcined at 800°C for 8 hours and cooled to obtain a spherical support. The surface roughness of the spherical support was tested with a surface roughness tester, and the Ra was 1955 nm and the Rz was 11852 nm.
[0055] The carrier a4 was prepared in the same manner as in Example 1. The surface roughness of the carrier a4 was measured, and Ra was 1162 nm and Rz was 6374 nm. The corresponding catalyst was prepared in the same manner as in Example 1 to obtain catalyst A4.
[0056] The attrition rate of catalyst A4 was measured according to the method of standard HG / T 2976-1999, and it was 0.21%. The powder ground off during the attrition rate test was collected, and the mass fraction of platinum in the powder was measured by elemental analysis, and it was 0.90%. The loss rate of active component platinum was 0.95%.
[0057] Comparative Example 1
[0058] A spherical support was prepared in the same manner as in Example 1.
[0059] Take 20g of γ-alumina, add water and wet ball mill to obtain a γ-alumina suspension aqueous solution. The particle size distribution of γ-alumina in the suspension is measured to be 19.7% of particles less than 2μm, 76.9% of particles with a particle size of 2-15μm, and 3.4% of particles with a particle size greater than 15μm. Take 80g of the above spherical support, spray the γ-alumina suspension aqueous solution onto the spherical support by atomization coating, and obtain a spherical catalyst carrier a5 with a shell structure after drying and calcining. The surface roughness of the carrier a5 is measured, Ra is 844nm, and Rz is 4603nm.
[0060] The corresponding catalyst was prepared in the same manner as in Example 1 to obtain catalyst A5.
[0061] The attrition rate of catalyst A5 was measured according to the method of standard HG / T 2976-1999, and it was 0.18%. The powder ground off during the attrition rate test was collected, and the mass fraction of platinum in the powder was measured by elemental analysis, and it was 0.96%. The loss rate of active component platinum was 0.88%.
[0062] Comparative Example 2 A spherical support was prepared in the same manner as in Example 1.
[0063] Take 20g of γ-alumina, add water and wet ball mill to obtain a γ-alumina suspension aqueous solution. The particle size distribution of γ-alumina in the suspension is measured to be 8.3% of particles less than 2μm, 73.2% of particles with a particle size of 2-15μm, and 18.5% of particles with a particle size greater than 15μm. Take 80g of the above-mentioned spherical support, spray the γ-alumina suspension aqueous solution onto the spherical support by atomization coating, and obtain a spherical catalyst carrier a6 with a shell structure after drying and calcining. The surface roughness of the carrier a6 is measured, Ra is 1975nm, and Rz is 10281nm.
[0064] The corresponding catalyst was prepared in the same manner as in Example 1 to obtain catalyst A6.
[0065] The attrition rate of catalyst A6 was measured according to the method of standard HG / T 2976-1999, and it was 0.44%. The powder ground off during the attrition rate test was collected, and the mass fraction of platinum in the powder was measured by elemental analysis, and it was 0.83%. The loss rate of active component platinum was 1.83%.
[0066] Comparative Example 3 A spherical support was prepared in the same manner as in Example 1.
[0067] Take 20g of γ-alumina, add water and wet ball mill to obtain a γ-alumina suspension aqueous solution. The particle size distribution of γ-alumina in the suspension is measured to be 1.6% of particles less than 2μm, 44.4% of particles with a particle size of 2-15μm, and 54.0% of particles with a particle size greater than 15μm. Take 80g of the above-mentioned spherical support, spray the γ-alumina suspension aqueous solution onto the spherical support by atomization coating, and obtain a spherical catalyst carrier a7 with a shell structure after drying and calcining. The surface roughness of the carrier a7 is measured, Ra is 2803nm, and Rz is 15753nm.
[0068] The corresponding catalyst was prepared in the same manner as in Example 1 to obtain catalyst A7.
[0069] The attrition rate of catalyst A7 was measured according to the method of standard HG / T 2976-1999, and it was 0.75%. The powder ground off during the attrition rate test was collected, and the mass fraction of platinum in the powder was measured by elemental analysis, and it was 0.78%. The loss rate of active component platinum was 2.93%.
[0070] Comparative Example 4
[0071] 1 kg of 300-mesh cordierite powder was extruded to form spherical particles with a diameter of 3 mm. After drying, the spherical particles were calcined at 1600°C for 8 hours and cooled to obtain a spherical support. The surface roughness of the spherical support was tested with a surface roughness tester, and the Ra was 1280 nm and the Rz was 6893 nm.
[0072] The carrier a8 was prepared in the same manner as in Example 1. The surface roughness of the carrier a8 was measured to be 853 nm Ra and 4566 nm Rz. The corresponding catalyst was prepared in the same manner as in Example 1 to obtain catalyst A8.
[0073] The attrition rate of catalyst A8 was measured according to the method of standard HG / T 2976-1999, and it was 0.63%. The powder ground off during the attrition rate test was collected, and the mass fraction of platinum in the powder was measured by elemental analysis, and it was 0.96%. The loss rate of active component platinum was 3.02%.
[0074] Application Examples
[0075] The catalysts prepared in Examples 1-4 and Comparative Examples 1-4 were respectively used in the production of styrene by dehydrogenation of ethylbenzene. The specific processes are as follows.
[0076] The hydrogen in the process of catalytic selective oxidation of saturated aromatic ethylbenzene to produce unsaturated aromatic styrene is carried out in a stainless steel reaction tube, and the catalyst filling amount is 30mL. The molar content of the reaction raw materials is styrene 2.4%, ethylbenzene 5.4%, benzene and toluene 0.08%, hydrogen 2.4%, oxygen 1.1%, nitrogen 0.11%, water 88.51%. The reaction temperature is 580℃, the reaction pressure is 100kPa, and the space velocity is 3h -1 The results are shown in Table 1 below.
[0077] Table 1
[0078] catalyst Hydrogen conversion rate % Oxygen conversion rate % Oxygen selectivity % A1 81.1 99.8 88.7 A2 82.7 99.9 91.5 A3 81.2 99.9 90.5 A4 81.0 99.8 89.4 A5 76.9 99.6 89.5 A6 80.2 99.5 86.6 A7 80.9 99.7 88.2 A8 80.8 99.8 88.5
[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A core-shell catalyst carrier, comprising a spherical support and an active component support layer wrapped on the outer surface of the spherical support, wherein: The surface roughness Ra value of the catalyst carrier is 900nm-1900nm, and / or the surface roughness Rz value of the catalyst carrier is 5000nm-10000nm.
2. The catalyst carrier according to claim 1, characterized in that The surface roughness Ra value of the catalyst carrier is 1400nm-1800nm, and / or the surface roughness Rz value of the catalyst carrier is 7000nm-9000nm.
3. The carrier according to claim 1 or 2, characterized in that The diameter of the catalyst carrier is 1-10 mm, preferably 2 mm-5 mm.
4. The catalyst carrier according to any one of claims 1 to 3, characterized in that The spherical support is selected from at least one of α-alumina, silicon carbide, spinel, mullite or cordierite; and / or The active component supporting layer is selected from at least one of γ-alumina, δ-alumina, θ-alumina or molecular sieve, preferably γ-alumina; and / or In terms of weight percentage, the weight ratio of the spherical support to the active component loading layer is (2-15):1, preferably (3-9):
1.
5. A method for preparing a core-shell catalyst carrier, comprising the following steps: (a) preparing a spherical support, wherein the surface roughness Ra value of the spherical support is between 1900nm and 2900nm, and the Rz value is between 10000nm and 20000nm; (b) Wrapping the active component loading layer material onto the surface of the spherical support.
6. The preparation method according to claim 5, characterized in that: In step (a), the preparation of the spherical support body comprises: preparing the powder of the support body material into spherical particles, and then calcining the spherical particles; Preferably, the calcination temperature is 800°C-1400°C, preferably 950°C-1300°C; Preferably, the calcination time is 2h-24h, preferably 4h-12h; Preferably, the spherical particles are prepared by rolling the support material into balls, extruding or centrifugally granulating; Preferably, the particle size of the support material is less than 100 mesh, preferably 300 mesh to 400 mesh; Preferably, the surface roughness Ra value of the spherical support body is 2100nm-2500nm, and Rz value is 11000nm-16500nm.
7. The preparation method according to claim 5 or 6, characterized in that: In step (b), the spherical support is coated with a solution containing an active component loading layer material by dip coating or atomization coating to achieve the encapsulation; Preferably, the solution containing the active component supporting layer material is obtained by wet ball milling; Preferably, in the active component supporting layer material, particles with a particle size less than 2 μm account for less than 10%, particles with a particle size of 2-15 μm account for 75%-90%, and particles with a particle size greater than 15 μm account for 5%-20%.
8. A spherical catalyst comprising a catalyst carrier according to any one of claims 1 to 4 or a catalyst carrier obtained by the preparation method according to any one of claims 5 to 7, and a platinum group metal supported on the catalyst carrier, Preferably, the platinum group metal is selected from one or more of ruthenium, rhodium, osmium, platinum and palladium, preferably platinum. Preferably, the weight of the platinum group metal is 0.01%-5.0%, preferably 0.05%-1.0% of the weight of the spherical catalyst.
9. A method for preparing a spherical catalyst, comprising: impregnating the catalyst carrier according to any one of claims 1 to 4 or the catalyst carrier obtained by the preparation method according to any one of claims 5 to 7 in an aqueous solution containing a platinum group metal element compound, and then drying and calcining. Preferably, the drying temperature is 60°C-200°C and the drying time is 2-24h; Preferably, the calcination temperature is 400° C.-800° C., and the calcination time is 2-12 hours.
10. A method for producing unsaturated hydrocarbons by dehydrogenating saturated hydrocarbons, comprising subjecting hydrogen produced by dehydrogenating saturated hydrocarbons to a selective oxidation reaction in the presence of the catalyst according to claim 8 or the catalyst prepared by the method according to claim 9; Preferably, the conditions of the selective oxidation reaction include a reaction temperature of 520-650°C, a reaction pressure of 20-200 KPa, and a liquid reaction space velocity of 0.1-10 h -1 .
Citation Information
Patent Citations
Composite carrier for preparing thin shell catalysts
CN102463143A
Method for preparing honeycomb ceramic catalyst
CN102872865A
Thin shell type catalyst and preparation method thereof
CN104437473A
Core-shell type catalyst carrier and coating catalyst
CN109331850A
Fischer-Tropsch synthesis catalyst, and preparation method and application thereof
CN110961096A
Cited By
Core-shell layered manganese-cerium-based bifunctional catalyst as well as preparation method and application thereof
CN121372455A
